PERUMUSAN DALAM KEBIJAKAN PENDIDIKAN DI INDONESIA - Herwani Herwani (CV. Adiba Aisha Amira, 2025)
The purpose of this writing is to describe a policy process that exists in the education system. Indonesia's national education system has determined that all forms of educational processes that exist in Indonesia must be implemented and developed to the fullest. In the education system there should be a decision, so that the policy process is expected to be right on target. In the education system, it is also necessary to have an agenda setting, this is done to attract the government's attention to the existing competition. In this case, a theoretical framework is needed so that policy formulation has direction and goals so that the policy formulation of an educational institution has legitimacy. Policy formulation is also inseparable from actors and policy formulation approaches.